Zein Beta-Cyclodextrin Micropowders for Iron Bisglycinate Delivery - Diletta Esposito; Giovanni Dal Poggetto; Aurélie Demont; Nicolai Kraut; Agnese Miro; Francesca Ungaro; Paola Laurienzo; Fabiana Quaglia (MDPI AG, 2020)
Given the limited number of materials available to design delivery platforms for nutrients, the rational combination of raw materials already approved as food ingredients and their processing through nano-micro technology can offer a unique tool for innovation. Here, we propose a nano-in-micro strategy to produce powders based on the hydrophobic protein zein, useful for the oral delivery of a hydrophilic iron source (iron bisglycinate) in anaemic patients. Iron-loaded powders were prepared through a two-step strategy consisting in the formation of a zein pseudolatex followed by a spray-drying step. To extend the manipulation space for zein and entrap iron bisglycinate, β-cyclodextrin (βCD) was selected as helping excipient. Addition of βCD allowed iron loading in the pseudolatex and greatly increased product yields after the drying process as compared to zein alone. Iron-loaded micro-sized powders were characterised by attenuated total reflectance−Fourier transform infrared (ATR-FTIR) spectra, thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC) to elucidate the role of βCD as a compatibilizer for the zein−iron system. Remarkably, micropowders released only 20% of FeBIS in a simulated gastric fluid, whereas release in a simulated intestinal fluid was almost completed in 7 h. In summary, βCD association to zein is a novel strategy to expand applications in the oral delivery of iron bisglycinate and, prospectively, to micronutrient chelates.